A Novel Tactile Web Navigator Device (University of Khartoum Engineering Journal, 2022)
In recent years, the internet has been a major source of information. Blind or visually impaired people have limited access to the internet; they may use screen readers, screen magnifiers, refreshable Braille displays or Braille printers. The level of user convenience provided by each tool is different and Braille display is found to be the most popular tool. Other tools have certain limitations on the speed of access and interaction. This paper presents a low cost novel tactile web navigator device aimed at enabling blind people to have feasible internet accessibility. This navigator design includes a microcontroller that communicates with the browser software running on the PC to acquire the text from a web page. The text is subsequently displayed using an array of solenoids which gives the required tactile sense. The blind user then uses his/her tactile sense to recognize the text in Braille language. It is recognized that only a small percentage of blind people are familiar Braille, another mode for output was developed which uses the English characters. The English characters may also appear in their conventional shapes to be sensed by the blind user. Many navigation functions like loading a webpage address, clicking on links and entering data (E-mails, passwords, etc) have been provided. The cost of the implementation is ~12% of the commercial Braille displays. The navigator was tested with volunteer blind users and the results were good; they were able to read Braille characters. Recording their notes, some limitations were discovered and will be eliminated in future models.